Role and mechanisms of mast cells in brain disorders - Huang, Xuanyu; Lan, Ziwei; Hu, Zhiping (Frontiers in Immunology, 2024)
Mast cells serve as crucial effector cells within the innate immune system and are predominantly localized in the skin, airways, gastrointestinal tract, urinary and reproductive tracts, as well as in the brain. Under physiological conditions, brain-resident mast cells secrete a diverse array of neuro-regulatory mediators to actively participate in neuroprotection. Meanwhile, as the primary source of molecules causing brain inflammation, mast cells also function as the "first responders" in brain injury. They interact with neuroglial cells and neurons to facilitate the release of numerous inflammatory mediators, proteases, and reactive oxygen species. This process initiates and amplifies immune-inflammatory responses in the brain, thereby contributing to the regulation of neuroinflammation and blood-brain barrier permeability. This article provides a comprehensive overview of the potential mechanisms through which mast cells in the brain may modulate neuroprotection and their pathological implications in various neurological disorders. It is our contention that the inhibition of mast cell activation in brain disorders could represent a novel avenue for therapeutic breakthroughs.